Estimating and forecasting the euro area monthly national accounts from a dynamic factor model - Elena Angelini; Marta Bańbura; Gerhard Rünstler (European Central Bank (ECB), 2008)
We estimate and forecast growth in euro area monthly GDP and its components from a dynamic factor model due to Doz et al. (2005), which handles unbalanced data sets in an efficient way. We extend the model to integrate interpolation and forecasting together with cross-equation accounting identities. A pseudo real-time forecasting exercise indicates that the model outperforms various benchmarks, such as quarterly time series models and bridge equations in forecasting growth in quarterly GDP and its components.
Keywords: E37; C53; 330; Dynamic Factor Models; Interpolation; nowcasting; Wirtschaftsprognose; Zeitreihenanalyse; Nationaleinkommen; Eurozone; EU-Staaten